Implementing ai-driven digital marketing strategies in fashion MSMEs: An analysis of adoption and entrepreneurial practices - Arfah, Lita (Trigin Publisher, 2025)
In the era of digital transformation, Artificial Intelligence (AI) is reshaping marketing practices, offering new opportunities for Micro, Small, and Medium Enterprises (MSMEs) in the fashion industry to enhance competitiveness and customer engagement. This study investigates the implementation of AI-driven digital marketing strategies within Micro, Small, and Medium Enterprises (MSMEs) operating in the fashion sector. As digital transformation accelerates, AI technologies such as chatbots, automated advertising, and data analytics offer significant potential to enhance marketing effectiveness and customer engagement. Using a quantitative descriptive design, data were collected through structured questionnaires from 132 purposively selected MSME entrepreneurs. The findings reveal that while there is a relatively high level of adoption for specific tools particularly chatbots and AI-based advertising a considerable proportion of businesses have yet to embrace AI comprehensively. Key benefits identified include increased marketing efficiency, improved customer targeting, and higher conversion rates. However, barriers such as limited technical knowledge, high implementation costs, and inadequate training persist. The study contributes to the understanding of digital innovation in small business marketing and offers practical insights for policymakers and stakeholders aiming to foster AI readiness and capability among fashion MSMEs.